Renal hypouricemia type 2 with SLC2A9 compound heterozygous variants: a case report of recurrent acute kidney injury triggered by low-intensity exercise - Paladugu, Niranjana Rekha; Vukkadala, Muralinath (Frontiers in Nephrology, 2024)
Renal hypouricemia (RHUC) is a rare genetic disorder characterized by impaired uric acid reabsorption which leads to persistently low serum uric acid levels. This condition predisposes individuals to complications such as uric acid kidney stones and exercise-induced acute kidney injury (EIAKI). Although mutations in SLC22A12 and SLC2A9 are commonly implicated in RHUC, the precise pathophysiological mechanisms, particularly those contributing to AKI, remain incompletely understood. We report the case of a 30-year-old male who experienced recurrent episodes of EIAKI despite the absence of high-intensity exercise, suggesting the involvement of factors beyond the traditional risk. Genetic analysis confirmed the diagnosis of RHUC type 2 (RHUC2) and identified compound heterozygous variants of SLC2A9. Although these variants are not novel, this case contributes to the limited literature on RHUC2, particularly in male patients with recurrent EIAKI. These findings highlight the importance of maintaining a high index of suspicion for RHUC in cases of unexplained AKI, especially when recurrent episodes follow physical activity, and the need for targeted genetic testing for an accurate diagnosis. The genomic data related to this case are available in Mendeley Data: Vukkadala, Muralinath; Paladugu, Niranjana Rekha (2024), “Renal hypouricemia,” Mendeley Data, V2, doi: 10.17632/7z84mkdgn9.2.